MD*ReX: Linking XploRe to standard spread-sheet applications - Gökhan Aydinli; Wolfgang Härdle; Torsten Kleinow; Hizir Sofyan (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
We will show a methodology of incorporating a profound statistical software environment into a standard spreadsheet application. Our approach is based upon a client/server computing philosophy, which will enable the user of our client side application to choose between various types of servers according to his needs of computing power.
urn:nbn:de:kobv:11-10048600
Keywords: 330